O pensamento estético de Nietzsche : a fisiologia na estética até a formulação da fisiologia da estética - Kaizer, Vitor Leandro (Universidade do Vale do Rio dos Sinos, 2020)
The present work aims to investigate the aesthetic thinking of the German philosopher Friedrich Nietzsche (1844-1900), from youth writings to the formulation of the physiology of aesthetics, which emerges from the late context of criticism of Richard Wagner’s music (1813-1883), in order to determine if it is possible to consider nietzschean aesthetic thinking pertinent to this period already as a certain “physiology of aesthetics”. In an effort to achieve this general objective, it was specifically and in a preliminary way, first: the aesthetic conception of the young Nietzsche; subsequently the tensions to which his initial aesthetic thinking is submitted during the intermediate period; and, finally, the way this confrontation made possible the final configuration of “aesthetics as applied physiology”. Therefore, the main writings relating to the first two phases, of Nietzsche were asked until the entry of the final phase, when the “physiology of aesthetics” is ultimately formulated as a greater objection to Wagnerian art. In the guise of conclusion, it can be affirmed that nietzschean aesthetic reflection is entirely permeated by the notion of physiology – as an axiological reflection on art –; since, when thinking about art, what the philosopher has in mind is to bring to light the essential value of art, that is, art as a possibility of life ,affirmation and dignification of existence; so that then physiology of aesthetics as a hermeneutic method of research – of art in its effects on the body and the psyche – is present in Nietzsche’s philosophical exercise before even assuming that formalized configuration.
Keywords: Nietzsche; Filosofia; Estética; Arte; Fisiologia; Nietzsche; Philosophy; Aesthetics; Art; Physiology; ACCNPQ::Ciências Humanas::Filosofia